Quality of life assessment in companion animals: what, why, who, when and how - Belshaw, Zoe (Wiley, 2018)
Quality of life is a commonly used phrase in veterinary medicine. It describes a complex evaluation that may be difficult for animals to perform, and the phrase “happiness” may be a more crude but useful approximation. Quality of life assessments should ideally be an integral part of our decision making, and should encompass evaluation of aspects of a pet’s life beyond just its health. Assessments should aim both to evaluate an animal’s quality of life, and to look for ways in which it might be improved. This article will discuss the challenges of assessing quality of life in companion animals, and will review the range of different methods available for assessment of quality of life in cats and dogs.